Nonreciprocal Pseudotyping: Murine Leukemia Virus Proteins Cannot Efficiently Package Spleen Necrosis Virus-Based Vector RNA - Certo, Jeanine L. (American Society for Microbiology, 1998)
It has been documented that spleen necrosis virus (SNV) can package murine leukemia virus (MLV) RNA efficiently and propagate MLV vectors to the same titers as it propagates SNV-based vectors. Although the SNV packaging signal (E) and MLV packaging signal (Ψ) have little sequence homology, similar double-hairpin RNA structures were predicted and supported by experimental evidence. To test whether SNV RNA can be packaged by MLV proteins, we modified an SNV vector to be expressed in an MLV-based murine helper cell line. Surprisingly, we found that MLV proteins could not support the replication of SNV vectors. The decrease in titer was approximately 2,000- to 20,000-fold in one round of retroviral replication. RNA analysis revealed that SNV RNA was not efficiently packaged by MLV proteins. RNA hybridization of the cellular and viral RNAs indicated that SNV RNA was packaged at least 25-fold less efficiently than MLV RNA, which was the sensitivity limit of the hybridization assay. The contrast between the MLV and SNV packaging specificity is striking. SNV proteins can recognize both SNV E and MLV Ψ, but MLV can recognize only MLV Ψ. This is the first demonstration of two retroviruses with nonreciprocal packaging specificities.